2011
DOI: 10.1089/cyber.2010.0012
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Specific Cues and Contexts Related to Smoking Craving for the Development of Effective Virtual Environments

Abstract: Craving is considered the main variable associated with relapse after smoking cessation. Cue Exposure Therapy (CET) consists of controlled and repeated exposure to drug-related cues with the aim of extinguishing craving responses. Some virtual reality (VR) environments, such as virtual bars or parties, have previously shown their efficacy as tools for eliciting smoking craving. However, in order to adapt this technology to smoking cessation interventions, there is a need for more diverse environments that enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Previous studies have demonstrated that heavy smokers experience greater craving for cigarettes than light smokers (García-Rodríguez et al, 2011;Kober et al, 2010). As a consequence, the reduction in craving produced by the treatment may be more noticeable.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have demonstrated that heavy smokers experience greater craving for cigarettes than light smokers (García-Rodríguez et al, 2011;Kober et al, 2010). As a consequence, the reduction in craving produced by the treatment may be more noticeable.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Previous research has also found that females show higher sensitivity than males to negative emotional cues (Carpenter et al, 2014;Colamussi, Bovbjerg, & Erblich, 2007;Saladin et al, 2012;Wray et al, 2015). There are other factors that have been related to greater craving for cigarettes, including younger age, higher nicotine dependence and symptoms of anxiety (García-Rodríguez et al, 2011;Sayette, Martin, Wertz, Shiffman, & Perrott, 2001;ThompsonLake et al, 2014;Watson et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, virtual world (VW) has penetrated into the real world (RW), and the clear boundary between RW and VW has begun to fade. This might result in transfer of behaviors gained in RW to VW 1,2 or vice versa. 3 In other words, the behaviors in RW and VW might be the parts of a continuum.…”
mentioning
confidence: 99%
“…The VR environments were developed on the basis of a previous study (García-Rodríguez et al, 2011) aimed at identifying frequent situations that produce smoking craving, as well as detecting specific craving cues in those contexts. In the environment breakfast at home, participants woke up and took a shower.…”
Section: Instruments and Variablesmentioning
confidence: 99%